Digital Education: Lithuania among Other European Union States - Moskvina, Julija (Acta Paedagogica Vilnensia, 2021)
Digital learning has become an everyday experience for a significant part of the population during a pandemic, regardless of their technical and psychological readiness. Both the more and less technologically advanced countries have faced the inevitable need for large-scale deployment of digital learning. This paper presents an assessment of the development of digital learning in Lithuania and the EU countries in 2019, i.e., before the pandemic began. The evaluation is carried out using the Index of Readiness for Digital Lifelong Learning, developed by the Center for European Policy Studies (CEPS) using official indicators and expert evaluation.Despite the growing number of studies aimed at assessing the digital divide in modern society and in education in particular, there is still a lack of empirical material to shed light on the link between the extent of digitalization, its determinants (such as national governance in promoting digitalization), and changes in learning outcomes caused by digitalization. The findings from the CEPS study presented in the paper are the first attempt to move beyond the assessment of the prevalence of learning digitalization in different European countries, taking a holistic view of digitalisation-induced changes in learning outcomes and participation with a special focus on digital learning policy as an important component of digitalisation development.The aim of this article is to assess the digital learning situation in Lithuania using the Index of Readiness for Digital Lifelong Learning, which was developed before the pandemic in 2019. The progress of European Union countries in developing digital learning is reviewed in the paper, based on the results of CEPS (2019) research. The Index of Readiness for Digital Lifelong Learning and the results of Lithuania’s assessment using the methodology developed by CEPS are presented here. The description of the situation in Lithuania is based on the second component of the Index titled “Institutions and policies for digital learning”.In order to qualitatively assess the country’s strategic provisions for digital learning, the method of analysis of the country’s strategic documents was applied. Public expert opinions were included into the analysis of the situation in Lithuania. An interpretation of the comparative analysis of the obtained index values is presented.Standard indicators from the Eurostat, Eurobarometer, OECD, Bertelsmann Stiftung, World Bank, and expert surveys were used to create the combined Index of Readiness for Digital Lifelong Learning. The index is constructed as a weighted average of indicators divided into three categories: learning participation and outcomes, institutions and policies for digital learning, and availability of digital learning. The assessment of the situation in the EU countries, carried out according to the developed methodology, allowed to calculate the value of the Index for each country. Lithuania ranks 11th in the overall EU-27 ranking with an Index value of 0.623.A more detailed analysis allowed us to see that the countries’ ratings can differ significantly according to the different categories of the Index. The Scandinavian countries lead in terms of learning participation and outcomes and, together with the Netherlands and Austria, in terms of availability of digital learning. Southern European countries received relatively high ratings in the Index category “institutions and policies for digital learning”, which reflects their determination to strengthen their position in the digital world. Estonia and the Netherlands also found themselves among the leaders in this category. Lithuania’s relatively high position in the list is also based on positive evaluations of the indicators of the second component of the Index (i.e., policies and institutions), while participation and learning outcomes were assessed modestly. Using the example of Lithuania, the article provides arguments in favor of why the second component of the Index should not be given.
Keywords: digital education; Index of Readiness for Digital Lifelong Learning; Lithuania